(untitled) (Hekima Review, 1994)
There is not only material poverty but also political instability and situation of war in many countries producing millions of refugees.Forty-two of the 54 African countries host refugees; recent estimates place the number of displaced people in Africa; at 22 million. Of these, six million are officially recognised refugees because they have actually crossed a border but sixteen million are displaced within their own country for political or tribal reasons. Statistics fall always short from reality because figures are increasing daily.